a Peran Supervisi Pendidikan dalam Meningkatkan Kualitas Pembelajaran: Pengertian Supervisi Pendidikan, Ruang Lingkup Supervisi Pendidikan, Tujuan dan Manfaat Supervisi Pendidikan, Prinsip-prinsip Supervisi Pendidikan, Peran Supervisi Pendidikan, Peran Supervisi Pendidikan dalam Meningkatkan Kualitas Pembelajaran - Nur Arifin, Rabiatul Adawiyah; Yakub , Ali Mustopa; Ropiah, siti; Asikin, Nurul; Siregar, Riskiani (STAIN Madina Press, 2025)
This study is grounded in the recognition that educational supervision plays a strategic role in improving instructional quality and teacher professionalism, as effective learning processes depend not only on curriculum and facilities but also on the continuous development of educators’ competencies. This research aims to describe the role, scope, principles, and contributions of educational supervision in enhancing teaching quality and supporting teacher development. The study employed a literature review method by analyzing relevant books, academic journals, and scientific articles related to educational supervision. The findings indicate that planned, democratic, and continuous supervision effectively identifies instructional weaknesses, provides constructive feedback, motivates teachers, and encourages innovation and professional growth. Academic supervision contributes to improving instructional practices, while managerial supervision strengthens administrative effectiveness within schools. Furthermore, the application of scientific, cooperative, and creative principles makes supervision more humanistic and productive for teachers. In conclusion, educational supervision serves as a systematic and collaborative developmental mechanism that significantly enhances learning quality while reinforcing teacher performance and professionalism.